Ejaculation Effect on Canine Prostatic Specific Esterase Serum Concentration - Alonge, Salvatore; Melandri, Monica; Leoci, Raffaella; Lacalandra, Giovanni M.; Caira, Michele; Aiudi, Giulio G. (Animals (Basel), 2020)
Canine prostatic diseases are usually asymptomatic in their onset and often identified in advanced stages. Canine prostatic specific esterase (CPSE) represents an early serum marker for prostatic diseases, also in asymptomatic dogs. The present study aimed to identify the effects of ejaculation on serum CPSE. Twenty adult intact male dogs were enrolled. Blood samples were collected to measure CPSE concentrations before (T0), immediately after (T1), and 24 h post (T2) ejaculation. Data were compared within and between groups by ANOVA (p < 0.05). Dogs were divided in two equal groups: A (healthy: CPSE ≤ 52.3 ng/mL at T0) and B (suspected for prostatic disorders: CPSE > 52.3 ng/mL or diagnosed with symptoms of prostatic diseases: CPSE > 90 ng/mL). CPSE was shown to be statistically higher in group B than A at any time point. In both groups, CPSE showed a significant increase at T1, and no significant differences between T0 and T2. This study demonstrates a definite effect of ejaculation on CPSE concentration. Twenty-four hours post-ejaculation, CPSE returns to basal values. Such physiological effects of ejaculation should be considered when planning analyses of CPSE concentrations, i.e., by respecting a proper sexual rest.